The effect of substrate on TiO2 thin films deposited by atomic layer deposition (ALD) - Hussin, Rosniza; Kwang, Leong Choy; Xianghui, Hou (Trans Tech Publications, Switzerland, 2015)
"ALD is a precision growth technique that can deposit either amorphous or polycrystalline thin films on a variety of substrates. The difference in substrate can cause a variation in the ALD process, even it is carried out using the same reactants and deposition conditions [1]. TiO2 thin films were grown using TTIP (Titanium isopropoxide) ALD on silicon wafers, glass slides, and stainless steel plates in order to study the effect of substrates on the growth of TiO2 with 3,000 deposition cycles, at 300oC.The thin films were analyzed using Xray Diffraction (XRD), Raman Spectroscopy, Atomic Force Microscope (AFM) and Spectroscopic Ellipsometer. The XRD analysis indicates that the main diffraction peak of (101) (2_= 25.3) could be indexed to anatase TiO2, regardless the types of substrates. The results show that crystalline TiO2 thin films could be grown easily on a crystal substrate rather than on an amorphous substrate."